Pengaruh Gross Domestic Product (GDP), Inflasi dan Profitability Terhadap Return Saham pada Sektor Infrastruktur yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2012-2019 - Piji Permana Putra; I Ketut Darma; Ita Sylvia Azita Azis (Warmadewa Economic Development Journal (WEDJ), 2022)
This study aims to see how big the influence of the company's internal factors, namely profitability (ROE) and the company's external factors, namely Gross Domestic Product (GDP) and Inflation on stock returns of the Infrastructure sector listed on the Indonesia Stock Exchange (IDX) for the period 2012 to 2019 as many as 19 company. The sample was determined using purposive sampling method, while the analytical method used was multiple linear regression model. The results of this study indicate that both internal and external factors simultaneously have a significant influence on stock returns. While partially the effect is different, Gross Domestic Product (GDP) and Profitability (ROE) each have a positive and significant effect, while Inflation has a negative and significant effect.